2011
DOI: 10.1258/ebm.2011.011165
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity suppresses sevoflurane preconditioning against myocardial ischemia–reperfusion injury: role of AMP-activated protein kinase pathway

Abstract: Obesity is a major risk factor for coronary artery disease, but its impact on anesthetic-induced cardioprotective actions is unexplored. We tested whether obesity inhibits anesthetic sevoflurane-induced preconditioning and whether this effect is mediated via the AMP-activated protein kinase (AMPK) signaling pathway. Sprague-Dawley rats were fed a high-fat (HF, 45% kcal as fat) or low-fat (LF, 10% kcal as fat) diet for 12 weeks. HF-fed rats developed metabolic disturbances including visceral obesity, hyperinsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 39 publications
4
43
0
Order By: Relevance
“…Multiple intracellular mechanisms, including the activation of protein kinase C, mitogen-activated protein kinase, adenosine receptors and mitoK ATP channels, have been indicated to be involved in anesthetic preconditioning-induced cardioprotection and neuroprotection (8,10,20). It is widely accepted that the activation/opening of mitoK ATP channels is a significant mechanism for ischemic preconditioning-induced protection in various organs and for ischemic postconditioning-induced cardioprotection (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple intracellular mechanisms, including the activation of protein kinase C, mitogen-activated protein kinase, adenosine receptors and mitoK ATP channels, have been indicated to be involved in anesthetic preconditioning-induced cardioprotection and neuroprotection (8,10,20). It is widely accepted that the activation/opening of mitoK ATP channels is a significant mechanism for ischemic preconditioning-induced protection in various organs and for ischemic postconditioning-induced cardioprotection (10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anesthetic postconditioning by modulation of reperfusion rather than ischemia may be more clinically useful for cardioprotection, as well as for neuroprotection. It has been demonstrated that pathological situations, including obesity, may affect the effectiveness of well-established cardioprotective strategies (7,8). However, the majority of studies regarding anesthetic postconditioning-induced neuroprotection have been conducted in healthy animals (4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, uncertainty remains. Preconditioning using volatile anaesthetic agents appears to work less well in animal models of hyperglycaemia and hypercholesterolaemia [5,6], precisely those situations in which we perceive the greatest perioperative risk. However, do rabbits and cardiac myocytes adequately model the metabolic syndrome?…”
Section: Preconditioningmentioning
confidence: 99%
“…Both genetic deletion and diet-induced obesity are widely used to replicate characteristics of metabolic syndrome in humans [6,18,20,23,25,27,[30][31][32][33]. According to the International Diabetes Federation (IDF), the metabolic syndrome is defined as a person having central obesity (a waist circumference≥94 cm for men, and≥80 cm for women) plus any two of the following four factors including raised triglyceride level (≥150 mg/ dL), reduced HDL cholesterol level (<40 mg/dL in males, and <50 mg/dL in females), raised blood pressure (systolic BP≥ 130 mmHg, Diastolic BP≥85 mmHg), and raised fasting plasma glucose levels (≥100 mg/dL).…”
Section: Obese-insulin Resistant Models and Changes In Metabolic Paramentioning
confidence: 99%
“…Either high-fat or high-carbohydrate food is usually chosen to induce obese-insulin resistance. Previous studies demonstrated that a high-fat diet (HFD) could increase body weight, plasma insulin, leptin, and cholesterol levels [13,22,33,34], indicating the development of obese-insulin resistance. Insulin sensitivity is also impaired in HFD-fed rats as indicated by increased blood glucose levels during an oral-glucose tolerance test (OGTT) [22].…”
Section: Obese-insulin Resistant Models and Changes In Metabolic Paramentioning
confidence: 99%